Predicting the Potential Distribution of Lagotis Medicinal Plants on the Qinghai‐Xizang Plateau, With a Maximum Entropy Model - Huiyuan Ma; Bo Wang; Xue Yang; Guoying Zhou (Ecology and Evolution)
ABSTRACT Lagotis is a Tibetan medicine with high medicinal and research value in the Qinghai‐Xizang Plateau region. Predicting its potential suitable areas can provide important references for the protection and research of Lagotis. This study investigated and collected 769 site data of six species of Lagotis and 28 environmental factor data, and used the maximum entropy model (MaxEnt) to simulate the distribution of suitable areas under three climate scenarios (RCP2.6, RCP6.0, RCP8.5) in the 2050s and 2070s. The results showed that: (1) The AUC values of the model training dataset for the six Lagotis species were all > 0.94, indicating that the predictions of the model were accurate. (2) Altitude (alt), isothermality (bio3), and average annual precipitation (bio12) were the main environmental factors affecting the geographical distribution of Lagotis. (3) Under the current climate conditions, with the increase of greenhouse gas emission concentration, the suitable distribution areas for the Lagotis genus plants are primarily located in the eastern, central, and southern parts of the Qinghai‐Xizang Plateau. (4) Compared to the present period, the suitable areas of Lagotis integra, Lagotis angustibracteata, and Lagotis ramalana potential distribution area will expand in the future. The area of high suitability for Lagotis macrosiphon shows an increasing trend. The area of moderate suitability for Lagotis brachystachya is decreasing, while the area of high suitability is increasing. In contrast, the suitable area of Lagotis brevituba decreased greatly. (5) The study found that Lagotis genus plants are suitable for survival in high‐altitude, low‐temperature areas. The research findings provide a basis for the cultivation and breeding of medicinal plants in the Qinghai‐Xizang Plateau, the migration protection, and the construction of nature reserve communities.